Mathematical Modelling of Endosulfan Adsorption Using Activated and Unactivated Boiler Fly Ash and Maize Cob - Osu, Bright; J.C, Igwe; C, Olunkwa; C.U , Aghalibe; K.E , Onwuka (Indonesian Journal of Modern Science and Technology, 2025)
The application of pesticides to control plant pests and increase yield introduces issues of pesticide contamination and toxicity. Endosulfan, a persistent organic pollutant, poses serious ecological and public health risks due to its toxicity, persistence, and bioaccumulative nature. Conventional remediation methods are often costly and generate secondary waste, hence the need for sustainable, low-cost alternatives. This work investigated the mathematical modelling of endosulfan adsorption from aqueous solutions using activated and unactivated boiler fly ash and maize cob. Batch adsorption experiments were conducted to examine the effects of contact time, initial concentration, and activation of adsorbents. The behavior of pesticide adsorption data against certain isotherm and kinetic equations was also investigated. The physicochemical properties of the activated and unactivated maize cob and boiler fly ash, as well as FT-IR, XRD, and SEM of the adsorbents, were determined. Both initial pesticide concentration and contact time affected the adsorption capacity of the adsorbents. As the initial concentration increased, the amount of pesticide adsorbed also increased. An increase in contact time rapidly increased the amount adsorbed until it reached a maximum at 60 minutes, after which it decreased; hence, equilibrium was reached after 60 minutes. Activation enhanced the porosity, cation exchange capacity, and surface functional groups of the adsorbents. Activated maize cob exhibited the highest adsorption capacity, followed by activated boiler fly ash, while unactivated forms showed comparatively lower performance. Equilibrium data fitted best to multilayer and heterogeneous surface models, while kinetic analysis suggested chemisorption tendencies. Activated maize cob and boiler fly ash are effective, eco-friendly, and low-cost adsorbents for the removal of endosulfan from aqueous systems. Mathematical modelling provided predictive insights into adsorption behavior, supporting process optimization. The findings demonstrate the potential of agricultural and industrial residues as sustainable alternatives for pesticide remediation and environmental protection.